Level of motivation in project-based learning of JKE students In POLISAS / Lian Ai Fang, Marliana Mahamad and Kafiza Ahmad Kamaruzzaman - Lian, Ai Fang; Mahamad, Marliana; Ahmad Kamaruzzaman, Kafiza (UiTM Cawangan Johor Kampus Pasir Gudang, 2020)
In education, appropriate teaching method is very important to determine the students' motivation during teaching and learning process. Therefore, a paradigm shift needs to be implemented from teacher-based approach to student-based approach in order to enhance students' intrinsic motivation. Hence, project-based learning is one of the student-based teaching methods that will enhance students' intrinsic motivation. Typically, there are five elements in project-based learning which are autonomy, authentic problem, skills, cooperative learning and teacher's roles. Therefore, this research is aimed to determine the level of intrinsic motivation that is contributed by each element of project-based learning. The samples were selected randomly comprising 115 fourth semester students undertaking Diploma in Electrical Engineering during the December 2019 session from Polytechnic of Sultan Haji Ahmad Shah. This research was a survey that utilised questionnaire as the research instrument. Through Statistical Package for Social Science (SPSS) Version 26.0, the collected data was analysed for mean scores. The results showed that in project-based learning, all elements contributed to high level of intrinsic motivation. Based on the research findings, future research on project-based learning should be continued so that the project based-learning can be used as one of the teaching methods that will enhance students' interest and motivation in line with advancement of education system.